Analysis of Factors Affecting Foreign Portfolio Investment in Indonesia for the Period 2005-2023 - Any Widayatsari; Cut Endang Kurniasih; Desrita Angelica (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the factors that affect foreign portfolio investment (FPI) in Indonesia. This research is motivated by the discovery of a phenomenon where there is a downward trend in portfolio investment and is not in line with the gross domestic product which has increased. This is not in accordance with asset demand theory and Harry Markowitz theory. The research method used is the Autoregressive Distributed Lag (ARDL) model processing technique which aims to see the factors that affect foreign portfolio investment in the long term and short term. The results showed that in the short term the BI Rate has a negative and significant effect on foreign portfolio investment in Indonesia and the exchange rate has a negative and significant effect on foreign portfolio investment in Indonesia. In the long term Gross Domestic Product (GDP) and Inflation have a negative and insignificant effect on foreign portfolio investment in Indonesia, interest rate BI Rate has a positive and significant effect on foreign portfolio investment in Indonesia and the exchange rate has a negative and significant effect on foreign portfolio investment in Indonesia. From these results it is suggested that the government needs to maintain the stability of the BI Rate and exchange rate, and the government also needs to create a conducive portfolio investment climate.